La desigualdad sociogeográfica en la prevalencia de anemia en niños - Pari Olarte, Josefa Berta; Zagaceta Guevara, Zaira; Chacaltana Ramos, Luz Josefina; Quispe Ilanzo, Melisa Pamela; Almeida Donaire, Roberto Santiago; Oyola García, Alfredo; Solano García, Cecilia Guiliana; Almeida Galindo, José Santiago (Sociedad Iberoamericana de Informacion Cientifica, 2024)
Background: Anemia in children is a major public health problem in the world and Perú, especially in those under three years old. Aim: The study was designed to identify the social determinants that explain the socio-geographic inequality in the distribution of anemia prevalence in six-to-35-month Peruvian children. Methods: An observational, ecological, and analytic study was carried out in 26 subnational governments of Peru. Correlation tests, simple and multiple linear regression, and calculating inequality gaps and gradients were applied. Results: The proportion of pregnant women without iron supplementation was the only explanatory variable for the prevalence of anemia in children under 36 months. The absolute gradient of inequality reflected a pattern of equity (ICI = 0.02). Excess of anemia prevalence in six-to-35-month children was equivalent to 11.53% along the gradient determined by the proportion of pregnant women without iron supplementation. Territories in the quintile with the highest proportion of pregnant women without iron supplementation had the highest gap in absolute and relative terms (18.49% and 1.46%; respectively). Conclusions: The proportion of pregnant women without iron supplementation would explain the socio-geographic inequality gap in the prevalence of anemia in 6-to-35-month Peruvian children. In other words, territories with the lowest achievement of this indicator would be exposed to a higher prevalence of anemia, so universal interventions must be focused on them.

Introducción: La anemia en niños, especialmente en menores de tres años, es un importante problema de salud pública en el mundo y en el Perú. Objetivo: Identificar los determinantes sociales que expliquen la desigualdad sociogeográfica en la distribución de la prevalencia de anemia en niños peruanos de 6 a 35 meses. Métodos: Se realizó un estudio observacional, ecológico y analítico en 26 gobiernos subnacionales del Perú. Se aplicaron pruebas de correlación, regresión lineal simple y múltiple, así como el cálculo de las brechas y gradientes de desigualdad. Resultados: La proporción de gestantes sin suplementación de hierro fue la única variable explicativa de la prevalencia de anemia en niños en la muestra evaluada. El gradiente absoluto de desigualdad reflejó un patrón de equidad (ICD = 0.02) con exceso de prevalencia de anemia en niños de 6 a 35 meses equivalente a 11.53% a lo largo del gradiente determinado por la proporción de gestantes sin suplementación de hierro y mayor impacto en los territorios ubicados en el quintil con mayor proporción de gestantes sin suplementación de hierro, en términos absolutos y relativos (18.49% y 1.46%; respectivamente). Conclusiones: La proporción de gestantes sin suplementación de hierro explicaría la brecha de desigualdad sociogeográfica en la distribución de la prevalencia de anemia en niños peruanos de 6 a 35 meses de tipo marginal. Los territorios con menor logro de este indicador estarían expuestos a mayor prevalencia de anemia, por lo que se requerirían que las intervenciones universales sean focalizadas en ellos.
Keywords: Children anemia; Health inequalities; Iron supplementation; Social determinants of health; https://purl.org/pe-repo/ocde/ford#3.03.05